INCREASING KNOWLEDGE IN PREGNANT WOMEN ABOUT ANEMIA SCREENING AND TRIPLE ELIMINATION THROUGH PREGNANT WOMEN CLASSES - Suryanih Suryanih; Resi Galaupa (Lembaga Pengembangan Kinerja Dosen, 2023)
According to the World Health Organization, the number of new HIV cases worldwide will approach 1.5 million by 2020. Africa is registered as the region with the highest number of new HIV cases with 880,000 cases. According to UNAIDS, around 50% of people living with HIV are women and 2.1 million are children under 15 years of age. Based on Indonesia's health status in 2018, 69.95% of pregnant women were tested for HIV and hepatitis B. Of these tests, 0.28% of pregnant women were HIV positive. The effect that HIV-infected pregnant women can transmit HIV to your child during pregnancy, childbirth or breastfeeding. In addition to the triple elimination test, anemia examination is also recommended for pregnant women, because it is one of the steps to prevent anemia in pregnant women. The purpose of this study was to increase pregnant women' s knowledge about anemia screening and determine triple elimination through pregnant women courses. The research method uses Quasy experimental design with a group pretest design. The sample in this study were all pregnant women in the Kampung Bojong Jaya area as many as 40 people, the sampling technique was a comprehensive sample. The results of the research are the knowledge of pregnant women about anemia screening and triple elimination before counseling, most pregnant women have sufficient knowledge and then have good knowledge. Pregnant women received the most information about anemia screening and three times the elimination in the pregnant women category (p-value 0.000). The research method uses Quasy experimental design with a group pretest design. The sample in this study were all pregnant women in the Kampung Bojong Jaya area as many as 40 people, the sampling technique was a comprehensive sample. The results of the research are the knowledge of pregnant women about anemia screening and triple elimination before counseling, most pregnant women have sufficient knowledge and then have good knowledge. Pregnant women received the most information about anemia screening and three times the elimination in the pregnant women category (p-value 0.000). The research method uses Quasy experimental design with a group pretest design. The sample in this study were all pregnant women in the Kampung Bojong Jaya area as many as 40 people, the sampling technique was a comprehensive sample. The results of the research are the knowledge of pregnant women about anemia screening and triple elimination before counseling, most pregnant women have sufficient knowledge and then have good knowledge. Pregnant women received the most information about anemia screening and three times the elimination in the pregnant women category (p-value 0.000). The results of the research are the knowledge of pregnant women about anemia screening and triple elimination before counseling, most pregnant women have sufficient knowledge and then have good knowledge. Pregnant women received the most information about anemia screening and three times the elimination in the pregnant women category (p-value 0.000). The results of the research are the knowledge of pregnant women about anemia screening and triple elimination before counseling, most pregnant women have sufficient knowledge and then have good knowledge. Pregnant women received the most information about anemia screening and three times the elimination in the pregnant women category (p-value 0.000).